Antiinflammation and antidsbiotic actions of flavancontent means on rat colon mucosa after received the peroxide sunflower oil - Bocharov, A. V. (Journal of Education, Health and Sport, 2017)
Aim: To determine prophylactics action of flavancontent means after introduction the peroxide sunflower oil. Materials and methods: Its were used flavancontent means: quertulin (quercetin + inulin + Ca citrate), lequin (lecithin + quercetin + inulin + Ca citrate) and lecasil (lecithin + flavolignan from Silybum marianum + Ca citrate). Rats received peroxide sunflower oil (PSO) per os in dose 1 ml/rat day. The flavancontent means introduced every day in dose 300 mg/kg in during 2,5 months. The activities elastase, urease, lysozyme, catalase and content of MDA were determined into colon mucosa. Results: The activities elastase, urease and content of MDA were increased in rats, what received PSO, but activity of lysozyme was reduced. The flavancontent means were lowered the activities of elastase and content of MDA, but was increased activity lysozyme. Conclusion: PSO made dysbiosis and inflammation into colon mucosa. The flavancontent means made prophylactic action, better lequin and lecasil.